Beyond Transactions: How Motivation, Trust, and Emotion Shape Generation Z Online Shopping in Indonesia: A Systematic Literature Review - Hasisiq Kharisma Fahmi; Ike Dwiastuti; Ninik Setiyowati (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The rapid expansion of digital commerce has reshaped the consumption patterns of Generation Z, positioning online shopping not only as a transaction process but also as an experience shaped by psychological mechanisms. This study conducted a systematic literature review to synthesize the results of empirical research on the roles of motivation, trust, and emotion in determining online shopping behavior of Generation Z in Indonesia. Ten peer-reviewed journal articles meeting eligibility criteria were selected through a structured review and critical evaluation process. The thematic aggregation revealed that motivation, especially hedonistic motivation, acts as the primary trigger for purchasing decisions through pleasure, satisfaction, and digital exploration. Trust functions as a psychological mechanism to mitigate perceived uncertainty and risk, allowing motivating impulses to be converted into purchasing intentions. Emotions act as reinforcing factors in decision-making in which positive emotions amplify purchasing behavior, and negative emotions can be suppressed even when motivation and trust are high. The integrated findings indicate that Generation Z's online shopping decisions are driven by the interaction of cognitive-motivating and emotional determinants, not purely rational choices. This study highlights the need to conceptualize online shopping behavior as a psychological system rather than a transactional system and suggests that future empirical studies should develop and validate conceptual models that incorporate motivation, trust, and emotion in the context of a digital consumer environment in Indonesia.Ekspansi perdagangan digital yang cepat telah membentuk kembali pola konsumsi Generasi Z, memposisikan belanja online tidak hanya sebagai proses transaksi tetapi juga sebagai pengalaman yang dibentuk oleh mekanisme psikologis. Studi ini melakukan Systematic Literature Review (SLR) untuk mensintesis hasil penelitian empiris tentang peran motivasi, kepercayaan, dan emosi dalam menentukan perilaku belanja online Generasi Z di Indonesia. Sepuluh artikel jurnal yang ditinjau sejawat yang memenuhi kriteria kelayakan dipilih melalui tinjauan terstruktur dan proses evaluasi kritis. Agregasi tematik mengungkapkan bahwa motivasi, terutama motivasi hedonistik, bertindak sebagai pemicu utama keputusan pembelian melalui kesenangan, kepuasan, dan eksplorasi digital. Kepercayaan berfungsi sebagai mekanisme psikologis untuk mengurangi ketidakpastian dan risiko yang dirasakan, memungkinkan impuls motivasi diubah menjadi niat membeli. Emosi bertindak sebagai faktor penguat dalam pengambilan keputusan di mana emosi positif memperkuat perilaku pembelian, dan emosi negatif dapat ditekan bahkan ketika motivasi dan kepercayaan tinggi. Hasil terintegrasi menunjukkan bahwa keputusan belanja online Generasi Z didorong oleh interaksi kognitif-motivasi dan determinan emosional, bukan murni pilihan rasional. Studi ini menyoroti perlunya mengkonseptualisasikan perilaku belanja daring sebagai sistem psikologis daripada sistem transaksional, dan menyarankan bahwa studi empiris masa depan harus mengembangkan dan memvalidasi model konseptual yang menggabungkan motivasi, kepercayaan, dan emosi dalam konteks lingkungan konsumen digital di Indonesia.